Mechanisms of Metabolism Interaction Between p-Cresol and Mycophenolic Acid. (19th November 2019) - Rong, Yan; Kiang, Tony K L
Abstract: Mycophenolic acid (MPA) is commonly prescribed for preventing graft rejection after kidney transplantation. The primary metabolic pathways of MPA are hepatic glucuronidation through UDP-glucuronosyltransferase (UGT) enzymes in the formation of MPA-glucuronide (MPAG, major pathway) and MPA-acyl glucuronide (AcMPAG). p -Cresol, a potent uremic toxin known to accumulate in patients with renal dysfunction, can potentially interact with MPA via the inhibition of glucuronidation. We hypothesized that the interaction between MPA and p -cresol is clinically relevant and that the estimated exposure changes in the clinic are of toxicological significance. Using in vitro approaches (ie, human liver microsomes and recombinant enzymes), the potency and mechanisms of inhibition by p -cresol towards MPA glucuronidation were characterized. Inter-individual variabilities, effects of clinical co-variates, in vitro-in vivo prediction of likely changes in MPA exposure, and comparison to other toxins were determined for clinical relevance. p -Cresol inhibited MPAG formation in a potent and competitive manner ( K i =5.2 µM in pooled human liver microsomes) and the interaction was primarily mediated by UGT1A9. This interaction was estimated to increase plasma MPA exposure in patients by approximately 1.8-fold, which may result in MPA toxicity. The mechanism of inhibition for AcMPAG formation was noncompetitive ( K i =127.5 µM) and less likely to be clinically significant. p -Cresol was the most potent inhibitor of MPA-glucuronidation compared with other commonly studied uremic toxins (eg, indole-3-acetic acid, indoxyl sulfate, hippuric acid, kynurenic acid, and 3-carboxy-4-methyl-5-propyl-2-furanpropionic acid) and its metabolites (ie, p -cresol sulfate and p -cresol glucuronide). Our findings indicate that the interaction between p -cresol and MPA is of toxicological significance and warrants clinical investigation.